Comparison of Functional Capacity using Primary Percutaneous Coronary Intervention with Pharmacological Therapy on ST Elevation Acute Coronary Syndrome Patients - Andini Nurkusuma Wardhani; Chaerul Achmad; Sunaryo B. Sastradimaja (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Acute Coronary Syndrome (ACS) is a shift manifestations pattern of ischemic myocardium. Revascularization either with Primary Percutaneous Coronary Intervention (PCI) or pharmacological therapy is an optional treatment for ST Elevation Acute Coronary Syndrome (STEACS) patients. The aim of the study was to compare the functional capacity using six-minute walking test on STEACS patients who underwent Primary PCI or pharmacological therapy.Methods: A cross sectional study was conducted from September to October 2012 to 35 STEACS patients who were treated after two years. The samples were obtained from the list of patients at Dr. Hasan Sadikin General Hospital. Inclusion criteria consisted of patients diagnosed as STEACS, cooperative and not experiencing cognitive disturbance. The exclusion criteria were STEACS patients with unstable angina or myocardial infarct in the last month, stable exertional angina, and pregnant women. The patients underwent 6 minutes walking test,VO2max was measured using theCalahin and Cooper formula, then Metabolic Equation Task (METs) was calculated. Data were analyzed by unpaired T-test.Results: There were 19 Primary PCI and 16 pharmacological therapy patients. The average of age between the two groups was distributed evenly. Most of the STEACS patients were male, had a college/academic degree and were retired. Patients treated with pharmacological therapy had higher average of VO2 max and METs than patients with Primary PCI. There was no significantly differences of METs between those groups (p>0.05)Conclusions: There were no significantly differences of functional capacity in STEACS patients treated with Primary PCI or Pharmacological therapy. [AMJ.2015;2(1):162–6]